2022
DOI: 10.1021/acsami.2c14212
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding High-Resolution Quantum Dot Color Converters with Small Pixel Sizes

Abstract: Designing the next generation of high-resolution displays requires high pixel density per area and small pixel sizes without compromising the optical quality. Quantum dots (QDs) have been demonstrated as a promising material system for down-conversion of blue emission as they provide pure colors on the wide color gamut. However, for high color-conversion efficiency, the required QD film thickness has not been compatible with small pixel sizes. In this work, we develop a new type of freestanding QD-based color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Mixing QDs with photosensitive materials, such as PR, is a simple method for fabricating photopatternable QD films. [92][93][94][95][96][97][98][99][100] Because the technical strategy for the high-resolution patterning of PR is well developed, highly luminescent QD-PR composite patterns should be formed directly via photolithography by employing commercial PR. Because photolithography is a welldeveloped technique, a controllable thickness and fine patterning capability can be achieved for highly luminescent QD-PR composite patterns.…”
Section: Photosensitive Compositementioning
confidence: 99%
“…Mixing QDs with photosensitive materials, such as PR, is a simple method for fabricating photopatternable QD films. [92][93][94][95][96][97][98][99][100] Because the technical strategy for the high-resolution patterning of PR is well developed, highly luminescent QD-PR composite patterns should be formed directly via photolithography by employing commercial PR. Because photolithography is a welldeveloped technique, a controllable thickness and fine patterning capability can be achieved for highly luminescent QD-PR composite patterns.…”
Section: Photosensitive Compositementioning
confidence: 99%
“…As the easiest of the three bonding methods to realize, QD-Polymer formed by polymer-coated QDs is usually simply a blend of the photosensitive polymer monomer and QDs. [58][59][60][61][62][63][64][65][66][67][68][69][70] Therefore, it can be adapted to most experimental environments and allows for easier control of pattern parameters by direct photolithography. Many studies have indicated that numerous photosensitive polymers available in the market can be uniformly mixed with QDs.…”
Section: Direct Photolithography Patterning Of Polymer-coated Quantum...mentioning
confidence: 99%
“…27,28 Each light-emitting unit in a large-area region can be controlled independently in this kind of technology resulting in high-contrast displays, and high-quality luminous materials help to realize the high-purity color and the wide color gamut. 29–31 But the industry procedure and technology are not mature now, and they still face problems in realizing both stable materials and low-cost manufacturing.…”
Section: Introductionmentioning
confidence: 99%